Creep of alkali-activated cement mixtures. (June 2022) - Hojati, Maryam; Rajabipour, Farshad; Radlińska, Aleksandra
Abstract: Alkali activated Cement (AAC) is one of the alternatives to ordinary portland cement (OPC) and recently attracted a lot of attention due to its environmental benefits as a sustainable construction material for building and infrastructures. However, one area of significance is related to long-term durability, especially in time-dependent deformation such as shrinkage and creep. The previous results of shrinkage tests of AACs validated the importance of curing temperature and creep in the volumetric stability of AACs. Thus, this work measured creep characteristics of four different AAC mortar cylinders over 20 months. The results were compared with the predicted creep values for ordinary portland cement mixtures calculated according to the ACI 209 method. The creep coefficient of fly ash-rich and slag-rich mixtures after 20 months of loading was about 2 and 4 times, respectively, larger than the predicted coefficient for portland cement mixtures. By applying nonlinear least squares estimation, a reliable equation (with R 2 > 96%) was proposed to predict the viscous response of each studied AAC mortar. The findings of this paper signified that slag-rich mixtures were much more prone to viscoelastic deformation under constant load, which resulted in larger drying shrinkage under internal drying stresses—as such, increasing the slag content in AACs led to a larger time-dependent (viscous) response. Additionally, it was observed that high curing temperature changed the creep response (different variables in the estimated equation), increased the maturity, and lowered the viscous response of AACs.